2012
DOI: 10.1245/s10434-012-2752-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Tumor-infiltrating Lymphocytes for Survival in Curatively Resected Stage IV Colon Cancer with Isolated Liver or Lung Metastasis

Abstract: High density of CD45RO(+) TILs showed independent prognostic significance for OS. This result may help to improve the prognostication of curatively resected stage IV colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 37 publications
5
59
0
Order By: Relevance
“…Although the density of TILs in the primary tumor was found to be associated with the chemotherapeutic outcome in this study, the correlation between the density of TILs in the metastatic tumor, which is a target for chemotherapy, and the chemotherapeutic outcome is unclear. A previous report described a strong correlation between the density of TILs in the primary tumor and that in metastatic tumors (28). Therefore, the evaluation of TILs in the primary tumor may serve as a substitution for the evaluation of TILs in metastatic tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Although the density of TILs in the primary tumor was found to be associated with the chemotherapeutic outcome in this study, the correlation between the density of TILs in the metastatic tumor, which is a target for chemotherapy, and the chemotherapeutic outcome is unclear. A previous report described a strong correlation between the density of TILs in the primary tumor and that in metastatic tumors (28). Therefore, the evaluation of TILs in the primary tumor may serve as a substitution for the evaluation of TILs in metastatic tumors.…”
Section: Discussionmentioning
confidence: 95%
“…TILs have been identified in various types of tumors, including lung cancer. Their existence has been found to be associated with decreased tumor progression (25), induction of responses to chemotherapy (26,27) and increased lifetime of patients (28). TILs derived from neonatal cord blood mononuclear cells induced marked human lung and cervical tumor remission in NOD/SCID mice, and the antitumor effect was accompanied with a high infiltration of CD3 + T cells in tumors and a marked induction of apoptotic cell death (25).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies showed that NK cells from patients with ovarian cancer have poor cytotoxic functions against tumors [31,32,33,34], and one study reported that high numbers of infiltrating NK cells in tumors was associated with a worse prognosis [35], which is in conflict with other reports on NK cell infiltration and outcome that focus on different types of cancers [36]. Studies have shown that the antitumor function of NK cells from peripheral blood of patients with ovarian cancer can be significantly augmented by in vitro stimulation with recombinant IL-2 [31,32], and that primary malignant ovarian cells are susceptible to killing by allogeneic NK lymphocytes.…”
Section: Introductionmentioning
confidence: 99%